Lyme Borreliosis as a Cause of Myocarditis in Pediatric Age - Constante, AD (2022)
Lyme borreliosis with myocarditis is rare in pediatrics and diagnosis requires a high index of suspicion. We present an adolescent with myocarditis, depressed left ventricular function, and evidence of Lyme borreliosis infection. Early recognition and treatment of Lyme disease can help to avoid serious complications.